A case of breast cancer with extensive colon metastasis. Issue 1 (27th November 2022) - Imai, Jin; Hanamura, Toru; Kawanishi, Aya; Ueda, Takashi; Mishima, Yusuke; Ito, Ayano; Shirataki, Yoshihiro; Morimachi, Masashi; Kodama, Toshio; Sato, Hirohiko; Kaneko, Motoki; Sano, Masaya; et al.
Abstract: Breast cancer is one of the most common malignancies in women worldwide. Although most breast cancers are curable, in cases of metastasis, many are often found in the lungs, bones, liver, and central nervous system; however, metastasis to the gastrointestinal tract is rare. Invasive lobular carcinoma, which represents only 5%–10% of breast cancers, has a higher risk of metastasis to the gastrointestinal tract than invasive ductal carcinoma. Here, we report a rare case of gastrointestinal metastasis of invasive lobular carcinoma that spread extensively to the colonic mucosa. Given the improved survival rates of breast cancer patients with current treatments, many rarer metastatic diseases, including gastrointestinal metastases, are likely to be increased in the future.